Environmental bottlenecks in children's genetic potential for adult socio-economic attainments: Evidence from a health shock. (2nd January 2019) - Fletcher, Jason M.
Abstract : This paper explores gene–environment interactions—interactions between family environments and children's genetic predispositions—in determining educational attainment. The central question is whether poor childhood family environments reduce children's ability to leverage their genetic gifts to achieve high levels of educational attainment—are there important 'bottlenecks' for poor children? The multigenerational information and genetic data contained in the United States' Health and Retirement Study are used to separate two mechanisms for intergenerational transmission of socio-economic status: genetic endowments and family environments. Using parental in utero exposure to the 1918–19 influenza pandemic as a source of quasi-experimental variation in family environments (that did not affect children's genetic endowments), I estimate interactions between parental investments and children's genetic potential. The main finding suggests that girls with high genetic potential whose fathers were exposed to influenza face reduced educational attainments—a gene–environment interaction—but there is no similar effect for boys.